THU0567 Prevalence and Significance of MEFV Gene Mutations in Patients with Sarcoidosis. (9th June 2015) - Kobak, S.; Sever, F.; Goksel, O.; Goksel, T.; Orman, M.; Berdeli, A.
Abstract : Background: Sarcoidosis is a chronic granulomatous disease. Pyrin, is encoded by the MEFV gene and has anti-inflammatory effects in the inflammasoma regulation. MEFV gene mutations affects the inflammatory cascade and cause familial Mediterranean fever. The relationship between different rheumatic diseases and MEFV gene mutations are shown in previous studies. Objectives: The aim of this study was to determine the MEFV gene prevalence in Turkish patients with sarcoidosis and to determine the possible correlation between the occurrence of mutations and disease phenotype. Methods: Seventy-eight sarcoidosis patients and age, gender and ethnicity compatible 85 healthy controls were included in the study. The most common eight MEFV gene mutations were investigated by PCR method. Results: Among seventy-eight sarcoidosis patients MEFV gene mutation was detected in nine patients (%11.5). The distribution of the nine mutations were as; three (3.8%) V726A, two (2.5%) E148Q, two (2.5%) M680, one (1.3%) A744S, one (1.3%) K695, respectively. None of the sarcoidosis patients were M694V, M694I, R761H and P369S and compound heterozygous carriers. MEFV gene mutations frequency in the healthy control group was found to be 22.4%.The distribution of MEFV gene mutations in the healthy control were; E148Q 9 (10.6%), M694V 2 (2.3%), M694I 1 (1.2%), M680 1 (1.2%), V726A 2 (2.3%), A744S1 (1.2%), K695 2 (2.3%), P369S1 (1.2%), respectively, Compared with the control group, a lower carrier frequency of MEFV gene mutations were detected in patients with sarcoidosis, but it was not statistically significant (p=0.067). In the sarcoidosis group, while serum ESR and CRP levels were significantly higher in the mutation carrier group than those of the non-carrier group (p=0.01, p=0.04). In the sarcoidosis group, while arthritis, enthesitis and ankle arthritis were significantly more frequent in the mutation carrier group than those of the non-carrier group (p=0.028, p=0.05, p=0.05 respectively). Conclusions: We found a lower frequency of MEFV gene mutations in Turkish patients with sarcoidosis compared with healthy control group. Sarcoidosis mutation carrier group were found to be associated with high serum acute phase response, arthritis and enthesitis. The presence of MEFV gene mutation may have a protective role for the development of sarcoidosis. Prospective studies with large patient series are need on this subject References: Newman LS, Rose CS, Maier LA. Sarcoidosis. New England Journal of Medicine 1997; 336: 1224±1234. Hofmann S, Franke A, Fischer A, et al. Genome-wide association study identifies ANXA11 as a new susceptibility locus for sarcoidosis. Nat Genet. 2008; 40:1103–1106. Yilmaz E, Ozen S, Balci B, et al. Mutation frequency of Familial MediterraneanFever and evidence for a high carrier rate in the Turkish population. Eur J Hum Genet 2001;9:553–5. Yigit S, Bagci H, Ozkaya O, et al. MEFV mutations in patients with familialMediterranean fever in the Black Sea region of Turkey: Samsun experience.J Rheumatol 2008;35:106–13. Tunca M, Akar S, Hawkins PN, et al. The significance of paired MEFV mutationsin individuals without symptoms of familial Mediterranean fever. Eur J HumGenet 2002;10:786–9. Disclosure of Interest: None declared